Non-linear cryptosystem utilizing biological mutation operation in the two-dimensional non-separable linear canonical transform domain - Sharma, Bhavana; Singh, Hukum; Rakheja, Pankaj; Khurana, Mehak (Oficyna Wydawnicza Politechniki Wrocławskiej, 2024)
This paper introduces a novel image encryption algorithm in the 2D-NSCT domain, employing a 4D hyperchaotic mapping, DNA coding with biological mutation, and the phase truncation and phase reservation (PTFT) operation. Unlike existing DNA-based encryption methods that heavily rely on the XOR operator, our proposed scheme integrates a biological mutation operator to enhance the security of the encryption process. The performance and effectiveness of our cryptosystem are thoroughly evaluated through comprehensive experiments and analysis on various grayscale images, including Cameraman, Peppers, and Baboon images. Simulation results are presented in this paper to demonstrate the performance of the proposed encryption algorithm. Notably, our algorithm exhibits high sensitivity to encryption parameters, and the utilization of DNA coding and PTFT adds an extra layer of security to the image encryption algorithm. To assess the resilience of our proposed algorithm, we conducted thorough simulations and subjected it to various challenges, including statistical attacks, noise attacks, occlusion attacks, classical cryptographic attacks, and special iterative attacks for asymmetric schemes, and along with brute-force attacks. The results validate the resilience of our proposed scheme and showcase its ability to withstand existing cryptographic attacks. Moreover, a comparative analysis was conducted to evaluate the performance of our proposed scheme against existing encryption algorithms of similar nature. The outcomes of this study clearly demonstrate that our encryption algorithm surpasses these existing schemes in terms of effectiveness and resilience against cryptographic attacks, affirming its superiority.
Optica Applicata, Vol. 54, 2024, nr 4, s. 581-607
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; cryptographic attacks; Matric; MSE; 2D-NSCT; PSNR